AI-based assessment: Aiken index analysis of content validity in scientific literacy instruments on the basic laws of chemistry with ethnochemistry - Zai, Fila Delfia; Yamtinah, Sri; Shidiq, Ari Syahidul; Widarti, Hayuni Retno; Wiyarsi, Antuni (Jurnal Pendidikan Kimia, 2024)
Scientific Literacy Assessment (SLA) is used to measure science literacy on basic chemical law material that has been qualified and tested. This study aims to prove the content validity of ethnochemistry SLA instruments integrated with artificial intelligence (AI) systems using Aiken's validity index so that they can measure students' scientific literacy in basic chemical law material. The research design uses the ADDIE development model (Analysis, design, development, implementation and evaluation which is simplified into analysis, design, and development. Content validity data was obtained from 10 experts, namely 7 chemistry education lecturers from UNS, UNY, and UM and 3 chemistry teachers in Surakarta through focus group discussions (FGD). The content validation test is based on aspects of context, language, and construct. A valid instrument is indicated by an Aiken index value of more than or equal to 0.73. The AI-integrated ethnochemistry SLA instrument on basic laws of chemistry material produced 15 valid items with an Aiken index greater than 0.73.